Shoulder Lameness in Dogs: Preliminary Investigation on Ultrasonography, Signalment and Hemato-Biochemical Findings Correlation - Grassato, Lisa; Drudi, Dario; Pinna, Stefania; Valentini, Simona; Diana, Alessia; Spinella, Giuseppe (Frontiers in Veterinary Science, 2019)
Forelimb lameness in medium and large breed dogs is frequently caused by traumatic or degenerative injuries of the shoulder. Patient history, physical examination, x-rays, blood and chemical work are routinely used to achieve diagnosis, and may be associated with ultrasonography or magnetic resonance imaging. Ultrasonography is increasingly popular in small animal practice due to its low cost, ease of repetition, and the fact that it is non-invasive and can be performed in conscious patients. It is also widely accepted that muscular stress or injuries can induce detectable variations in blood and chemical work. The aim of this preliminary study is to search for correlation between measurements of selected hematobiochemical parameters and ultrasound diagnosis in dogs affected by shoulder injuries. A retrospective study was conducted on orthopaedic clinical records of dogs presented to our Veterinary Teaching Hospital for lameness caused by shoulder problems over a period of 5 years. Dogs with both hematobiochemical and ultrasound examinations were selected. Patients were classified into 5 groups according to ultrasound diagnosis: 1) mild/moderate tendinopathy, 2) severe tendinopathy, 3) articular damage, 4) chronic myopathy and 5) neoplastic injury. Statistical analysis was performed to detect possible correlations between group and hematobiochemical parameters. Forty-four dogs met the inclusion criteria and forty-nine shoulders were diagnosed as injured. Significant differences were found between the age, sex, body weight, neutrophil count and AST levels. In particular, statistically significant increases were found for neutrophil count and AST concentration in case of ultrasonographically diagnosed severe tendinopathy, articular damage and neoplastic pathology. Further and wider studies are suggested to determine whether these biomarkers can become a useful diagnostic aid.